2020
DOI: 10.1007/s12182-019-00412-1
|View full text |Cite
|
Sign up to set email alerts
|

Wettability alteration and oil recovery by spontaneous imbibition of smart water and surfactants into carbonates

Abstract: Naturally fractured carbonate reservoirs have very low oil recovery efficiency owing to their wettability and tightness of matrix. However, smart water can enhance oil recovery by changing the wettability of the carbonate rock surface from oilwet to water-wet, and the addition of surfactants can also change surface wettability. In the present study, the effects of a solution of modified seawater with some surfactants, namely C 12 TAB, SDS, and TritonX-100 (TX-100), on the wettability of carbonate rock were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The data used in the present work was obtained from the open literature as well as our own experiments [4,25,[27][28][29][30]. As explained earlier, the data was collected so as to target three main functionalities minimizing permeability impairment (I), minimizing the possibility of scale damage in the field (II), maximizing oil recovery from matrix (III).…”
Section: Datamentioning
confidence: 99%
“…The data used in the present work was obtained from the open literature as well as our own experiments [4,25,[27][28][29][30]. As explained earlier, the data was collected so as to target three main functionalities minimizing permeability impairment (I), minimizing the possibility of scale damage in the field (II), maximizing oil recovery from matrix (III).…”
Section: Datamentioning
confidence: 99%
“…The wettability of solid surface has long been the spotlight of scientific research due to its substantial application in lubrication, waterproofing, antifouling, self-cleaning, and oil/water separation, in relation to industrial engineering applications such as in agricultural pesticide, electric power transmission, detergents, petroleum production, material modification, and biomedicine (Zheng et al 2010;Guo et al 2012;Song et al 2019;Rostami et al 2019;Ehsan et al 2019;Luo et al 2016;Sudha et al 2019;Ahmadi et al 2020). The fundamental theory of wetting is properly expressed by Young's equation (Young 1805), which describes the spontaneous wetting mechanism of a solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…Fern et al [8][9][10][11][12] used nuclear magnetic resonance imaging (MRI) to monitor the self-absorption process of the rock, studied the evolution process of percolation and oil recovery in core samples and found that reverse percolation and absorption only occurred in the first time [13]. Chapman [14] studied the influence of pore shape and throat width on fluid displacement through a microetching model and observed the distribution characteristics of oil and water in pores in the process of infiltration and absorption. However, the microetching model and the nuclear magnetic technology could only study the mechanism of percolation and absorption; hence, the variation characteristics of percolation and absorption could not be quantitatively described.…”
Section: Introductionmentioning
confidence: 99%